MENINGKATKAN PRESTASI BELAJAR SEJARAH MELALUI PENERAPAN MODEL PEMBELAJARAN MAKE A MATCH - Ni Wayan Sasih Artini (Jurnal Bakti Saraswati (JBS): Media Publikasi Penelitian dan Penerapan Ipteks, 2020)
Classroom action research was conducted in the second semester XI MIPA2 students of SMA Negeri 4 Denpasar in the academic year 2018/2019 which aimed to improve historical learning achievement through the application of the Make A Match learning model in class XI MIPA2 students in the second semester of SMA Negeri 4 Denpasar in the academic year 2018/2019.Data from the results of this study were collected by administering learning achievement tests. In analyzing the data obtained using descriptive analysis method.The data generated from this study consisted of preliminary data, cycle I data and Cycle II data. From the preliminary data it is obtained that the average new class reaches 69.75 and the learning completeness reaches only 30.56%. This data is far below expectations considering the KKM history subjects in SMA Negeri 4 Denpasar is 75.In the first cycle there has been an increase in the class average reached 73 and the percentage of mastery learning reached 52.78%.In the second cycle the average grade has reached 82.42 and the percentage of mastery learning has reached 94.44%. The data in Cycle II is in line with expectations due to the use of constructivist learning models. The conclusion obtained is the history of learning achievement can be increased through the application of the Make A Match learning model for students of class XI MIPA2 in the second semester of SMA Negeri 4 Denpasar in the academic year 2018/2019.